TEACHING WRITING RECOUNT TEXTS THROUGH BLOG - Marpaung, Uliana Sara; Sudarsono, Sudarsono; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research was conducted to find out whether or not Blog was significantly effective to teach writing recount texts and how effective the Blog was to teach writing recount text. This research was conducted to Year ? 8 students of SMPN 10 Pontianak in Academic Year 2017/2018. This research was a pre-experimental design with 2 meetings of instruction. There were 38 students of VIII B who participated in this research. In this research, the result of t-test computation was 9.38 with the degree of freedom is 39 and t-table is 0.005. It showed that null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that blog affects students? ability in writing recount text is accepted. In conclusion, blog can be a good alternative in teaching writing recount text to year ? 8 students of SMP Negeri 10 Pontianak. Key Words: Writing, Recount Text, Blog.